(untitled) (Research, Society and Development, 2021)
The fava beans crop, despite the somewhat restricted cultivation, has great socioeconomic importance for the state of Paraiba, due to its adaptability to ideal climate and soil conditions. Thus, this research aimed to evaluate the initial growth and physiology of fava beans accessions (Phaseolus lunatus L.) subjected to mineral fertilization and soil conditioners under Pombal-PB conditions. The experimental design used was a randomized block design with six repetitions, in a 10 x 2 factorial scheme, with two broad beans genotypes (Luzente and Venturinha) and ten treatments. The plants were subjected to the following treatments: T1 = control; T2 = NPK100%; T3 = NBarvar + PK100%; T4 = NBarvarr + PK100% + N50%; T5 = KBarvar + NP100%; T6 = KBarvar + NP100% + K50%0%; T7 = PBarvar + NK100%; T8 = PBarvar + NK100% + P50%; T9 = NBarvar + PBarvar + KBarvar; T10 = NBarvar + PBarvar + KBarvar + NPK50%. The growth variables stem diameter and number of leaves were evaluated, as well as the gas exchange variables CO2 assimilation rate, transpiration, stomatal conductance, internal CO2 concentration, instantaneous water use efficiency and instantaneous carboxylation efficiency. The highest values obtained for stem diameter and better responses to physiological parameters were observed in treatments that used soil conditioners via seeds and fertigation. The mineral NPK fertilization associated with soil conditioners can compose the nutritional management of the fava beans crop under the conditions in which the study was developed.